Ultra-Struktur Kayu Tekan Damar (Agathis loranthifolia Salisb.) dalam Hubungannya dengan Sifat Fisis Kayu Ultra Structure of Compression Wood of Agathis (Agathis loranthifolia Salisb.) and Its Relation to Physical Properties - I Ketut Nuridja Pandit; Istie Sekartining Rahayu (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
Compression-wood is one of the abnormalities phenomena found in softwood’s trunk. This abnormality has not been studied comprehensively yet as most of the research on normal trees. This research objective was to analyze ultra structure of Agathis compression wood cell walls and the relation to its physical properties. Wood samples were taken from compression wood in size of 0.5 cm x 0.5 cm x 3 cm.  Ultra structure of cell walls characteristics were analyzed descriptively by using SEM image, while physical properties studied were green and air dried moisture content, density and specific gravity, and shrinkage. The results showed that the form of tracheid cells were changed cross sectionally; intercellular spaces occurred between round tracheid cells; the third layer of secondary cell wall (S3) of compression wood was not clearly distinct; and the angle orientation of microfibril increased along the longitudinal axis. The ultra structure differences led to different physical properties such as greater moisture content, density as well as shrinkage